Extracorporeal Rewarming Is Associated With Increased Survival Rate in Severely Hypothermic Patients With Preserved Spontaneous Circulation - Podsiadło, Paweł; Smoleń, Agata; Brožek, Tomáš; Kosiński, Sylweriusz; Balik, Martin; Hymczak, Hubert; Cools, Evelien; Walpoth, Beat; Nowak, Ewelina; Dąbrowski, Wojciech; Miazgowski, Bartosz; Witt-Majchrzak, Anna; et al. (ASAIO journal (American Society for Artificial Internal Organs, 2023)
Treatment recommendations for rewarming patients in severe accidental hypothermia with preserved spontaneous circulation have a weak evidence due to the absence of randomized clinical trials. We aimed to compare the outcomes of extracorporeal versus less-invasive rewarming of severely hypothermic patients with preserved spontaneous circulation. We conducted a multicenter retrospective study. The patient population was compiled based on data from the HELP Registry, the International Hypothermia Registry, and a literature review. Adult patients with a core temperature <28°C and preserved spontaneous circulation were included. Patients who underwent extracorporeal rewarming were compared with patients rewarmed with less-invasive methods, using a matched-pair analysis. The study population consisted of 50 patients rewarmed extracorporeally and 85 patients rewarmed with other, less-invasive methods. Variables significantly associated with survival included: lower age; outdoor cooling circumstances; higher blood pressure; higher PaCO 2 ; higher BE; higher HCO 3 ; and the absence of comorbidities. The survival rate was higher in patients rewarmed extracorporeally ( p = 0.049). The relative risk of death was twice as high in patients rewarmed less invasively. Based on our data, we conclude that patients in severe accidental hypothermia with circulatory instability can benefit from extracorporeal rewarming without an increased risk of complications.
Keywords: dospělí; Retrospective Studies; retrospektivní studie; Extracorporeal Circulation; lidé; terapeutické zahřívání; Hypothermia; Survival Rate; hypotermie; míra přežití; nízká teplota; mimotělní oběh; Adult; Cold Temperature; multicentrické studie jako téma; Humans; Multicenter Studies as Topic; Rewarming